New Compression–Encryption Algorithm Using Chaos-Based Dynamic Session Key - Setyaningsih, Emy; Wardoyo, Retantyo; Sari, Anny Kartika (International journal on smart sensing and intelligent systems, 2018)
This research proposes New Compression–Encryption Algorithm Using Chaos-Based Dynamic Session Key (CEA-CBDSK) to encrypt image data. CEA-CBDSK consists of an algorithm to generate initial symmetric keys and an algorithm to encrypt image data using four dynamic session keys derived from the initial keys. The key generation uses Discrete Wavelet Transform, Arnold Cat Map, and Cipher Block Chaining, while the image encryption is performed using the session keys produced by the chaotic logistic map method. From the evaluation, it is proven that CEA-CBDSK is able to protect transmitted image data against ciphertext-only attack, statistical attack, and differential attack.